Conjugate Gradients - Sadowská, Marie; Kozubek, Tomás; Dostál, Zdeněk; Vondrák, Vít (Scalable Algorithms for Contact Problems, 2017)
We begin our development of scalable algorithms for contact problems by the description of the conjugate gradient method for solving.